SHORT COMMUNICATIONS. Comparison of Linear and Angular Cephalometric Lip Morphology among Malaysian Malay and Malaysian Chinese Population. - Mohammad Khursheed Alam; Munirah Ab Talib; Noor Shaheera Abdul Aziz; Rehana Basri; Kathiravan Purmal; Shaifulizan Abdul Rahman (International Medical Journal, 2014)
Objectives: The aims of this study were to evaluate and compare the cephalometric linear and angular measurements of lip morphology among Malaysian Malay and Malaysian Chinese population. Study Design: A retrospective study involving the collection and analysis of lateral cephalometric radiographs of Malaysian Malay and Chinese. Materials and Methods: Standardized cephalometric radiographs of 70 Malaysian Malay Adult and 70 Malaysian Chinese adults were analyzed. The cephalometric radiographs were collected from subjects aged from 18 to 25 years who did not undergo any orthodontic treatment. Total 9 linear and 5 angular measurements were carried out on cephalometric radiographs using Winceph 8.0 software. Descriptive statistics and racial dimorphism were analyzed using IBM SPSS Statistics Version 20.0. The reliability of the method was analyzed using Dahlberg's formula. Results: Statistically significant disparities were found between Malaysian Malay and Malaysian Chinese population in lower lip to H line and lower lip to B line. Conclusion: This study is an attempt to establish the description and comparison of cephalometric lip morphology between the Malaysian Malay and Malaysian Chinese adults.